A New Iridoid Glycoside from the Roots of Dipsacus asper - Zhonglin Yang; Haowei Yang; Jingyang Shen; Chunfeng Zhang; Jingzhi Li; De Ji (Molecules, 2012)
A new iridoid glycoside, named loganic acid ethyl ester (1), together with five known compounds: chlorogenic acid (2), caffeic acid (3), loganin (4), cantleyoside (5) and syringaresinol-4′,4′′-O-bis-β-D-glucoside (6) were isolated from the roots of Dipsacus asper. The structure of compound 1 was elucidated on the basis of detailed spectroscopic analyses. Lignan is isolated from Dipsacaceae species for the first time. Compounds 1, 4 and 5 had moderate neuroprotective effects against the Aβ25–35 induced cell death in PC12 cells.